Measuring TEFL Students’ Foreign Language Classroom Anxiety: A Rasch Analysis Approach - Dairabi Kamil; Daflizar Daflizar; Rodi Hartono; Toni Indrayadi (Edukasi, 2021)
This study sought to measures the foreign language classroom anxiety of the English Department students of a university in Indonesia and to compare the anxiety across independent demographic variables of gender and length of study at the department. The literature shows that foreign language learning anxiety affects one’s achievements in learning a foreign language. Data were collected through administration of the adapted version of Foreign Language Classroom Anxiety Scale to 96 students selected through stratified random sampling technique. The anxiety was assessed through Rasch analysis while analyses for significant difference in the anxiety across the two independent variables were conducted using tests of inferential statistics. The findings show the existence significant number of students who tend to be highly anxious in learning English. The findings also indicate a significant difference in the students’ anxiety across the independent variable of semester where semester 4 students tend to be more anxious than those of other semesters. No significant difference in the students’ anxiety was found across the independent variable of gender. The implications of these findings were then discussed.